Crossing boundaries – volume 1 : scientific career ; volume 2 : publications ; volume 3 : Living together in post-apartheid South Africa - (:unkn) unknown (My University, 2010)
This Habilitation thesis analyses within the framework of cultural and political geography contemporary South Africa cities through the example of Cape Town. It deals with compacted social change in emerging countries, using the post-apartheid South African example not as an exceptional case but as a lens to understand contemporary cities and the crafting of citizenship. Then, a territorial analysis of Cape Town highlights the persistence of segregation in the social and spatial structures of the city over the centuries, while showing how urban practices often subverted the overlaying structure. This analysis also shows the limits of spatial desegregation since the end of apartheid. Lastly, this thesis explores how urban practices both reshape the post-apartheid city and establish new places for learning how to live together, e.g. sacred spaces, places of memory and public spaces.
Keywords: African Research